SIGIRR modulates the inflammatory response in the brain - COSTELLO, DEREK; LYNCH, MARINA ANNETTA; MC QUILLAN, KEITH (Elsevier, 2010)
One of the more recently described members of the interleukin-1 (IL-1) receptor family, single-Ig-Interleukin-1 related receptor (SIGIRR), has been identified as a negative regulator of inflammation in several tissues. It modulates the responses triggered by stimulation of Toll-like receptor (TLR) 4 and IL-1 in several peripheral cell types, possibly in an NF?B-dependent manner. Consistently, responses to lipopolysaccharide (LPS) are exaggerated in SIGIRR-deficient mice and the symptoms of experimental inflammatory conditions are more profound in these animals. Here we set out to establish whether the absence of SIGIRR was associated with inflammatory changes in the brain and report that, LPS induced a greater effect on CD40 and ICAM mRNA in mixed glia prepared from SIGIRR-/-, compared with wildtype mice. This was associated with parallel changes in TNF? and IL-6 at mRNA and protein levels, an effect which was observed in purified microglia but not astrocytes. Similarly, LPS exerted a more profound effect on microglial activation and cytokine production in hippocampal tissue prepared from SIGIRR-/-, compared with wildtype mice. The effect of LPS on exploratory behaviour was also accentuated in SIGIRR-/- mice. The evidence suggests that these changes are a likely consequence of increased hippocampal expression of CD14 and TLR4, and NF?B activation in SIGIRR-/- mice.
PUBLISHED
Keywords: Neuroscience; Toll-like receptors (TLRs; SIGIRR; LPS; microglia; Cytokines; interleukin-1 (IL-1)